Lung Pseudomesothelioma in Patient with Asbestos Exposure: A Case Report - Devy Trianne Putri; Isnin Anang Marhana; Dhihintia Jiwangga Suta Winarno (Faculty of Medicine Universitas Airlangga, 2020)
Background: Pseudomesotheliomatous carcinoma is a rare case of lung cancer with marked pleural extension resembling malignant pleural mesothelioma on diagnostic imaging. One of tool to diagnose lung pseudomesothelioma is by performing thorocoscopy pleural biopsy. Diagnostic thoracoscopy also has a higher sensitivity than pleural fluid cytology and needle biopsy.Case: We report a rare case of pseudomesotheliomatous carcinoma of the lung in a 50-year-old man with asbestos exposure. The patient had complained of dyspnea and chest roentgenogram showed left pleural effusion. Computed tomography (CT) of the chest revealed diffuse irregular left pleural thickening and without a clear initial primary lesion found in both of lung parenchyma, which mimicked pleural mesothelioma. Pleural tissue sampling was performed to obtain definitive diagnosis by video-assisted thoracoscopic surgery. At the operation, the tumor was found to have spread along the pleural surface and primary lesion was not detected in the right lung parenchyma. Immunohistochemically, the tumor was positive for Thyroid Transcription Factor- 1 (TTF-1), but negative for calretinin, P63, and Neuron Specific Enolase (NSE). Final diagnosis was adenocarcinoma of the lung and patient had good clinical response to Gefitinib.Conclusion: Based on the results of clinical studies (images and clinical observations), although pseudomesotheliomatous in patient with asbestos exposure is difficult to distinguish from pleural mesothelioma, we have a case of pseudomesotheliomatous lung diagnosed by a thoracoscopic pleura biopsy. For such cases, thoracoscopic pleural biopsy should be performed at an early stage.